Attitudes Toward Democracy and Authoritarianism Before, During and After Military Rule. the Case of Chile, 1972–2013 - Osorio-Flores, R (Routledge, 2019)
Studies on attitudes toward democracy in post-authoritarian settings tend to overlook support for democracy before the authoritarian experience. Since authoritarian experiences are alleged to affect attitudes towards democracy and authoritarianism, we use the case of Chile to assess the determinants in support for democracy between 1972 and 2013. Estimating marginal effects and predicted probabilities for probit models on polls conducted before and after military rule (1973–1990), we find weak support for authoritarianism before 1973 and stable support for democracy before, during and after military rule. We also review public opinion polls for the authoritarian period to show stable support for democracy. Since democracy was restored, views on the military regime have worsened. The authoritarian experience did not change the determinants of attitudes toward democracy. Those in the middle class and leftists supported democracy more strongly before, during and after military rule. © 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group.